Competency-oriented education for sustainable development: Lessons from five courses on energy poverty. Issue 7 (9th October 2018) - Singer-Brodowski, Mandy; Grossmann, Katrin; Bartke, Stephan; Huning, Sandra; Weinsziehr, Theresa; Hagemann, Nina
Abstract : Purpose: Energy poverty can be seen as a relatively new, but typical sustainability problem in which various dimensions (ecology, society and economy) are interlinked and in part conflict with each other. Moreover, the variety of involved stakeholders (planners, tenants, housing companies, private landlords, energy consultants, etc.) represents conflicting aims for solving this problem. This paper aims to present a systematic linkage between higher education for sustainable development (HESD) and education about energy poverty yet. Design/methodology/approach: A qualitative comparative case study approach with a similar didactic approach is used. Findings: Based on the literature about HESD and an overall model in general didactics, ten criteria were identified and used for an overall reflection about similar courses dealing with the topic of energy poverty. The criteria covered the learning goals, the didactical approaches and the institutional support in the forms of organisation in the courses. Research limitations/implications: There was no competency measurement of the students in the described courses. Practical implications: There was no evaluation of the development of students' key competencies for sustainability. However, the reflections of students and teachers revealed a positive development regarding the students' learning process, especially because they worked on a real-world sustainability problem: energy poverty. Originality/value: This contribution describes how university courses on energy poverty were designed and implemented at five German universities. Against the background of general criteria for HESD, it reflects on the experiences that the use of this concept evoked. Through a comparison of the five courses against these criteria, the paper outlines strengths and weaknesses of the approach and closes with recommendations and requirements for designing further courses.